Effect of natural hydroxyapatite and β-tricalciumphosphate on dynamic changes in the mechanical properties of experimental compact bone defect - Korenkov, Olexiy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Objective: to compare the effects of natural hydroxyapatite and β-tricalcium phosphate (β-TCP) on the dynamics of changes in the mechanical properties of experimental defect of cortical bone. Methods: the experiment was performed on 48 white male rats. In the middle third of the femoral shaft reproduced perforated defect 2.5 mm in diameter to the medullary canal, which the animals of the 1st group filled osteoplastic materials «Cerabone®» (GA), and 2nd — «Сalc-i-oss®» (β-TCP). Fragments of the injured bone was investigated at 15, 30, 60, and 120 days by dynamic mikroindentition with the definition of micro-hardness and Young’s modulus of the field of implantation and osteoplastic materials adjacent the parent bone. Results: it was found that on the 15th day experiment microhardness and Young modulus of the defect area was predominantly caused by mechanical properties of the implanted material in its cavity («Cerabone®», «Сalc-i-oss®») and significantly exceeded those of the parent bone parameters. In the future, micro-hardness and Young’s modulus of implantation «Calc-i-oss®» gradually decreased and at 60 days. experiment are smaller than the parent bone in, and on the 120thday. r ose a nd caught up with her p erformance. Microhardness and Young’s modulus of implantation «Cerabone®» throughout the experiment remained unchanged and significantly exceeded the value obtained for the adjacent region and the parent bone implantation «Calc-i-oss®». <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Conclusions:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> using the «Cerabone®<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">» area of cortical bone defect becomes high and stable mechanical properties and osteoplastic material «Calc-i-oss®<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">» contributes to the full restoration of micro-hardness and rigidity of injury bathroom bones for 4 months.